Gonad maturation and spawning performance of the sand sea cucumber (Holothuria scabra) by Oodev® dan Ovaprim® administration - Sari, Dwi Ulta; Muzahar, Muzahar; Yulianto, Tri; Putri, Dwi Septiani; Zahra, Aminatul; Miranti, Shavika (Acta Aquatica: Aquatic Sciences Journal, 2023)
Sea cucumber (Holothuria scabra) contains lots of collagen and vitamin E for the pharmaceutical and cosmetic industries. H. scabra have high economic value. The price in the local market is IDR 400,000-1,200,000/kg and internationally it is IDR 500,000-IDR 5,000,000/kg dry weight. The level of exploitation is high, and it is suspected that there has been overfishing in several areas. Cultivation efforts need to be done to maintain the population in nature. The natural rate of gonad maturation and spawning in H. scabra broodstock is relatively slow, so efforts are needed to speed it up, among other things by administering hormones. This study aimed to stimulate (1) gonad maturation and (2) H. scabra spawning. The study used a completely randomized design (CRD) with 3 treatments and 3 replications in 2 stages using broodstock measuring 250-350 g/head. Stage 1: (1) Treatment A: without immersing the H. scabra in hormone solution, (2) Treatment B: immersing the H. scabra in the Oodev®/Oocyte developer dose of 1 mL/kg weight, and (3) Treatment C: soaking sea cucumber broodstock in Oodev® dose of 2 mL/kg weight. Stage 2: (1) without immersion of the broodstock in hormone solution, (2) immersion of the broodstock in Ovaprim® doses of 1 mL/kg weight. The data obtained were analyzed by analysis of variance. The results showed that immersion of H. scabra broodstock in Oodev® and ovaprim® was not successful in stimulating gonad maturation and spawning in H. scabra broodstock. The spawning behavior of sea cucumbers that were successfully observed included body movements such as writhing, coiling like a ball, sticking to walls, partially erecting their bodies, actively crawling, and being more active at night.Keywords: Gonad; Holothuria scabra; Oodev®; Ovaprim®; Spawning; Sea cucumber.